Cytotoxicity and anti-inflammatory effect of a novel diminazene aceturate derivative in bovine mammary epithelial cells. (July 2021) - Jia, Fang; Zhang, Xiangjun; Ma, Weiwu; Li, Xueqiang; Zhou, Xuezhang
Abstract: Diminazene aceturate (DA) has been used in the treatment of infections of trypanosomes in animals. Interestingly, its anti-inflammatory effect has recently gained increased interests. However, DA has been reported to have toxic side effects that limit its application. Therefore, we synthesized and screened a novel low-toxic DA derivative, namely the DA derivative 3 (DAD3). In the present study, anti-inflammatory effect of DAD3 was evaluated bovine mammary epithelial cells (BMECs) in vitro model. The results demonstrated that DAD3 had less cytotoxicity, and had a stronger effect in inhibiting secretion of inflammatory factors in BMECs, compared to DA. Mechanistically, DAD3 was able to inhibit the production of pro-inflammatory factors in part by suppressing the generation of mitochondrial reactive oxygen species (ROS) in BMECs upon LPS stimulation. Molecular analysis further indicated that DAD3 was capable of resolving inflammation in BMECs through a mechanism by preventing nuclear translocation of NF-p65, subsequently inhibiting transcription of inflammatory factors. In this context, DAD3 inhibited the phosphorylation of IκB, ERK, JNK and P-38 proteins of nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) signaling pathways. These results suggested the DAD3 was a novel DA derivative with low toxicity and strong anti-inflammatory effects in BMECs exposed to LPS, through a mechanism by blocking the NF-κB and MAPK signaling pathways. This study also provides an evidence that the DAD3 may be a novel anti-inflammatory agents warranted for further investigation in treatment of mastitis in cows. Highlights: A synthetic, novel and low toxicity diminazene aceturate derivative (DAD3) was screened in vitro. DAD3 inhibited the secretion of pro-inflammatory factors. DAD3 repaired inflammation is based on inhibition of the NF-κB and MAPK signaling pathways.